How We Still Fail Rape Victims: Reflecting on Responsibility and Legal Reform - Shen, Francis X. (Columbia Journal of Gender and Law, 2019)
Despite over thirty years of rape law reform, rape remains too prevalent, and successful convictions of rapists remain too rare. I argue in this Article that we continue to fail rape victims because we are too quick to give in to our instinct to blame and less willing to engage in the careful reflection that would lead us to see more profoundly our collective responsibility for this failure. The Article proceeds in five sections. In Section I, I review a number of studies and argue that rape reforms to date, while significant, have nonetheless been inadequate. I then discuss the pervasiveness of rape myths about blame, both over time and in the present day. In Section II, I extend my analysis to rape in the tort system. Drawing on a recent empirical analysis of jury verdicts and settlements, as well as interviews with practicing plaintiffs’ attorneys, I argue that unless harm is concrete and visible, we tend to devalue it. In Section III, I turn my attention to policymaking. Based on a series of empirical studies, I discuss the role of the media and legislators in shaping policy response to sex crimes. I argue that the policy response has often been driven by moral panic rather than careful reflection. In Section IV, I evaluate why reform has failed and suggest that the impulse to blame all men or all men in fraternities is overly simplistic. In Section V, I conclude the paper with a reflection on the deeper meanings of rape myths and rape law reform. I argue that to find lasting solutions for the problems of sexual violence we must first look inward. Reflection, leading to collective responsibility and collective action, is the best path to reform.